Conversion Disorder: The Challenges in Diagnosing - Atiqah Chew Abdullah; Pang, Nicholas Tze Ping; Walton Wider; Asma Perveen (WHO Office in Azerbaijan, 2022)
Conversion disorder is defined as a psychiatric illness in which symptoms and signs affecting voluntary motor or sensory function cannot be explained by a neurological or general medical condition. To assess the biological and psychosocial factors of a person with conversion disorder and to provide appropriate psychotherapy to the client. A Single case study design was carried out with the case of conversion disorder. The client’s level of understanding about the illness, symptoms, and functionality improved as evidenced by the subjective report and reduction of anxiety and symptoms post-test. In this case, CBT and supportive therapy are effective in managing the client’s conversion disorder symptoms.